THE STUDY OF THE BANK SYARIAH INDONESIA MERGER BASED ON SWOT ANALYSIS - Muhammad Fikry Aransyah (Jurnal MD, 2021)
As a country with the largest Muslim population globally, Indonesia can become a leader in the Islamic financial industry. The increased public awareness of halal matters and stakeholders’ strong support are essential factors in developing the halal industry ecosystem in Indonesia. The Islamic banking industry in Indonesia itself has experienced a significant increase and development in the past three decades. Product innovation, service improvement, and network development show a positive trend from year to year. The spirit to accelerate is also reflected in the number of Islamic banks that take corporate actions. Sharia banks owned by State-owned banks are no exception, namely Bank Syariah Mandiri, BNI Syariah, and BRI Syariah. Indonesia uses the SWOT approach. This study uses a literature study where the data come from literature related to the title under study. In this study, the authors collected the data from existing research and summary reports on mergers carried out by 3 Islamic banks, namely BRI Syariah Bank, Mandiri Syariah Bank, and BNI Syariah Bank. It can be concluded that Bank Syariah Indonesia has massive capital strength and sources of funds, regulation, facilities, and support from the government and already has m-banking BSI Mobile. The weaknesses of Bank Syariah Indonesia are less competitive business models and products, less optimal quality and quantity of human resources, integration problems and corporate culture, ecosystems, and information technology that are still lagging behind conventional banks. The opportunities for Bank Syariah Indonesia are penetrating markets that were previously inaccessible, the increasing number of investors in the Islamic capital market, global Sukuk financing, the financial technology ecosystem, the efforts by the government and academia in growing digital and financial inclusion, and the large Muslim population in Indonesia. The threats that arise are the low literacy and inclusion of the Islamic banking system, the increasing risk of financing liquidity problems, the ratio of non-performing financing, and competitors’ better financial technology. It was suggested that mergers exploit synergies, reduce overlaps in operations, right-sizing, and redeploy surplus staff either by retraining, restructuring labor, or voluntary retirement. The merger likewise meets the need for development, diminishing the degree of rivalry, and making an enormous substance between State-owned Islamic banking enterprises.